DOI: 10.3990/1.9789036535120
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory feedback at daily physical activity patterns

Abstract: Table of contents Chapter 1 General introduction Chapter 2 Daily physical activity of patients with the chronic fatigue syndrome: A systematic review Chapter 3 Deviations in daily physical activity patterns in patients with the chronic fatigue syndrome: A case control study Chapter 4 Ambulatory feedback at daily physical activities in treatment of the chronic fatigue syndrome Chapter 5 Ambulatory feedback at daily physical activities in treatment of chronic fatigue syndrome: A randomized controlled trial Chapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Over the last years we have been working on a large number of physical activity motivation studies in which motivational messaging was included. Results have been published from studies targeting various chronic diseases such as COPD [6], Chronic Fatigue Syndrome [36] or Chronic Low Back Pain [5]. The messages used in these studies were all comparable (with minor variations), and consisted of a total of 24 (4 neutral, 11 encouraging and 9 discouraging), e.g.…”
Section: Modeling Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the last years we have been working on a large number of physical activity motivation studies in which motivational messaging was included. Results have been published from studies targeting various chronic diseases such as COPD [6], Chronic Fatigue Syndrome [36] or Chronic Low Back Pain [5]. The messages used in these studies were all comparable (with minor variations), and consisted of a total of 24 (4 neutral, 11 encouraging and 9 discouraging), e.g.…”
Section: Modeling Contentmentioning
confidence: 98%
“…This may seem obvious, as for most physical activity promotion tools, encouraging activity is the only goal. However, for various chronic disease patient populations such as Chronic Obstructive Pulmonary Disease [6], Chronic Fatigue Syndrome [36] or Chronic Low Back Pain [5], a ''secondary'' goal is identified to balance activity levels over the day. This means that sometimes -e.g.…”
Section: High Level Modelmentioning
confidence: 99%
“…No matter the technology or the treatment models used, the problem arises when treatment adherence is low. For some user populations, like the elderly, the level of adherence decreases over time [1] [2] and this creates the need for creating motivation for users. Gamification strategies can fit motivation patterns for most user groups, including the elderly and the PLWD, in order to maximize the use of eHealth technologies and the expected benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine supports them in maintaining a healthier lifestyle that maintains autonomy, independence and quality of life. Adherence to telemedicine interventions is related to improved health outcomes (Huis in 't Veld et al, 2010), but is low and decreasing over time (Tabak et al, 2014, Evering et al, 2013. A possible explanation for the drop in adherence is the lack of motivation given by a professional in face-to-face contact, or plain boredom.…”
Section: Introductionmentioning
confidence: 99%
“…User engagement, which is key to adherence, is known to significantly increase when preferences of the user are effectively met (Petty et al, 1979, Bakkes et al, 2012. Our previous research showed several classifications, to categorise both younger and older users (De Vette et al, 2015), based on for example ingame behaviour or gaming motivation.…”
Section: Introductionmentioning
confidence: 99%